PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN KONSUMEN BENGKEL DINAN MOTOR - Ishaq Pasha Padilla Kusdiansyah; Netty Nurlenawati; Dexi Triadinda (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2026)
This study aims to analyze the extent to which facilities and service quality affect customer satisfaction at Bengkel Dinan Motor in Karawang. In this study, a quantitative approach was used through a survey method. Purposive sampling was used as the sampling method, and 97 consumers were respondents. Data were collected by distributing questionnaires and analyzing multiple linear regression using the SPSS program. To determine how customer satisfaction, both partially and simultaneously, is influenced by facilities and service quality at Bengkel Dinan Motor in Karawang. The results of the study show that service quality and facilities have a significant positive influence on customer satisfaction simultaneously and partially. An Adjusted R Square value of 0.819 indicates that 81.9% of the variation in customer satisfaction can be explained by service quality and facilities, while the rest is influenced by variability outside the research model. This study provides a theoretical contribution to the development of customer satisfaction studies and a practical contribution as evaluation material and recommendations for Bengkel Dinan Motor to continuously improve service quality and facilities. In addition, service quality and facilities are important factors in improving customer satisfaction.